HUBUNGAN ORIENTASI PROFESIONAL DAN KOMITMEN PROFESI TERHADAP KONFLIK PERAN DENGAN VARIABEL MODERASI PARTISIPASI ANGGARAN DAN ORIENTASI TUJUAN SISTEM ORGANISASI - Erlisa Norma Wijayanti (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2018)
The purpose of this research is to analyze the influence of professionalorientation and professional commitment to role conflict, with budgetparticipation and goal orientation of organizational system as moderation.This research uses primary data type is quantitative and data obtainedthrough questionnaire. The sample in this research is auditor in semarang asmuch as 88 auditor, covering 18 public accountant office in semarang,questionaire which return as many as 53 questionnaires. Data wereanalyzed using regression with the help of SPSS program (statisticalproduct ang service solutions) 19.The results of this study are professional orientation and professionalcommitment influencing role conflict, budget participation does not moderatethe influence of professional orientation to role conflict, and the orientation oforganization's system goals does not moderate the influence of professionalcommitment to role conflict.